Macrophage Migration Inhibitory Factor: Critical Role in Obesity, Insulin Resistance, and Associated Comorbidities - Robert Kleemann; Richard Bucala (Mediators of Inflammation)
Obesity is associated with insulin resistance, disturbed glucose homeostasis, low grade inflammation, and comorbidities such as type 2 diabetes and cardiovascular disease. The cytokine macrophage migration inhibitory factor (MIF) is an ubiquitously expressed protein that plays a crucial role in many inflammatory and autoimmune disorders. Increasing evidence suggests that MIF also controls metabolic and inflammatory processes underlying the development of metabolic pathologies associated with obesity. This is a comprehensive summary of our current knowledge on the role of MIF in obesity and obesity-associated comorbidities, based on human clinical data as well as animal models of disease.